Pengaruh Pemotongan Co-Axial Pada Proses Pemesinan Turn-Milling Terhadap Kekasaran Material Aluminium 6061 - Fajar Pratama Putra; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Turn and milling processes in machining can be referred as turn-milling processes, where working tool and cutting tool works simultaneously. So in this cutting proces, the chip is produced by a cutting tool that is tangent on the bottom part. The main factor in the machining process is the result of surface roughness. The method of this research is using co-axial turn-milling by applying variations to the rotational speed of the tool and the speed of rotation of the workpiece, so the surface quality produced influences by the parameters of the machining process in the form of tool rotation speed and workpiece rotation speed. The purpose of this research is to find out the surface roughness value and to determine the effect of tool rotation speed and workpiece rotation speed on the surface roughness value of aluminum 6061. In result, the higher the rotational speed of the tool and the speed of rotation of the workpiece, the roughness value on the 6061 aluminum workpiece will be smaller. Based on the roughness class, the parameter of tool rotation speed is 2500 rpm with the workpiece rotation speed of 800 rpm is the best parameter in this study with a roughness value of 0.862 µm. Keyword : Turn-milling, Co-axial, Tool rotation speed, Workpiece, Surface roughness.